Dispositivo para medição da impedância de aterramento de torres de linhas de transmissão - Pedro Mattioli Laborne El Awar (2020)
This master’s dissertation describes a new version of a device developed for the record and measurement of the grounding impulse response for application in the measurement of tower footing impulse impedance of transmission line towers and in the estimation of the corresponding low-frequency resistance value. The results and analysis of the laboratorial and field experimental tests performed are approached to assess the performance of the device. In order to reach the objective of this dissertation, three meters were developed. The first and second ones have an embedded 500 V impulse generator, as the prototype version of the original meter. The third one has a 1000 V impulse generator and external filtering module that is connectable to the voltage measuring circuit. Specific hardware and firmware were developed. The hardware includes analog electronic modules, consisting of an impulse generator, auxiliary power source circuits and acquisition and signal conditioning circuits, all controlled by a digital signal processor where the firmware is embedded. Furthermore, the device allows the record of 41 tests and is capable to transfer data to a computer through serial protocol RS-232. Experimental tests showed that the third version of the meter presents operational characteristics and configuration desired for application in the assessment of the impulse response of transmission line grounding electrodes. It is a low cost and low weight device, robust and of stable operation. The instrument, independently fed by batteries, has resources for instantaneous verification of the measurement consistency, notably a LCD display for visualizing the current impressed to the grounding electrode and ground potential rise waveforms during the test. Is also includes an internal flash memory, which is a resource for the complete record of each test data and for its transfer to a computer in order to perform a digital signal processing. In particular, tests pointed out a good performance of the meter associated with a specific measurement methodology that uses the OATL (open-ended artificial transmission line) set up, which makes possible to reduce the distance of the current measurement circuit to about 20 m.